PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PEMECAHAN MASALAH MATERI STATISTIKA UNTUK KELAS VI SD - Indah Lestari Setiorini (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
In mathematics learning the use of student work sheet is still limited. In addition the learning ofmathematics in schools is still not effective. For it is necessary to develop a problem-based worksheets toengage students in active learning mathematics. This study used a developmental research 4-D that hasbeen modified. Result of the validation and testing of the problem based worksheets developed shows thatstudent work sheet is valid, practical, and effective at